2018
DOI: 10.1111/cup.13389
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic dermatosis of hematologic malignancy: Correlation of molecular characteristics of skin lesions and extracutaneous manifestations of hematologic malignancy

Abstract: Background Skin diseases are frequent in patients with chronic lymphocytic leukemia (CLL) and other hematological neoplasias. Eosinophilic dermatosis (ED) of hematologic malignancy has long been considered a nonspecific cutaneous reaction pattern. Recently neoplastic cells have been shown to be present in ED, thus challenging the classification as a nonspecific dermatosis. Methods We report five patients with ED in association with CLL. We further investigated the presence of neoplastic B‐cells in the skin inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…One of the most intriguing debates concerns the role of leukaemic cells in EDHM. Many studies of patients with B-cell chronic lymphatic leukaemia with EDHM demonstrated the presence of neoplastic B cells within the inflammatory infiltrate of the skin lesions [110,113,121]. However, this is not a specific finding of EDHM, as these cells can be similarly detected in many inflammatory skin diseases as well as in close proximity of skin cancers occurring in patients with B-cell chronic lymphatic leukaemia [122].…”
Section: Eosinophilic Dermatoses Of Haematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most intriguing debates concerns the role of leukaemic cells in EDHM. Many studies of patients with B-cell chronic lymphatic leukaemia with EDHM demonstrated the presence of neoplastic B cells within the inflammatory infiltrate of the skin lesions [110,113,121]. However, this is not a specific finding of EDHM, as these cells can be similarly detected in many inflammatory skin diseases as well as in close proximity of skin cancers occurring in patients with B-cell chronic lymphatic leukaemia [122].…”
Section: Eosinophilic Dermatoses Of Haematological Malignanciesmentioning
confidence: 99%
“…3 a, b) [ 103 , 112 ]. Additional histopathologic features include dermal oedema, dermal-epidermal detachment, eosinophilic spongiosis and parakeratosis [ 113 ]. In patients presenting with blisters and histological evidence of dermal-epidermal detachment, direct immunofluorescence of perilesional skin or serum tests usually fail to identify autoantibodies against BP180 or other proteins of the dermal–epidermal junction [ 114 ].…”
Section: Eosinophilic Dermatoses and Related Skin Manifestationsmentioning
confidence: 99%
“…3,4 The world literature on eosinophilic dermatosis of hematologic malignancy (EDHM) was recently reviewed 5 ; to the best of my knowledge, 206 patients with this condition have been described (Table I). [3][4][5][6][7] EDHM has been observed more frequently in men (55% [107 of 193 patients]) than in women (45% [86 of 193 patients]); sex was not provided for 13 patients.…”
mentioning
confidence: 99%
“…However, lymphomas, other leukemias, and other hematologic disorders have also been observed in these patients (Table I). [3][4][5][6][7] To date, this condition has not been described in individuals with solid tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation